Right Lower Quadrant Abdominal Pain in a Patient with Prior Ventriculoperitoneal Shunting: Consider the Tip! - Petros Charalampoudis (Case Reports in Medicine)
Introduction. Ventriculoperitoneal (VP) shunting is the treatment of choice for nonobstructive hydrocephalus. In patients with such a device, right lower quadrant abdominal pain can puzzle the surgeon, posing a differential diagnostic problem among appendicitis, nonsurgical colicky pain, and primary shunt catheter tip infection. Treatment is different in either case. Presentation of Case. We hereby present a case of a young woman with prior ventriculoperitoneal shunt positioning who presented to our department with right lower quadrant abdominal pain. The patient underwent a 24-hour observation including a neurosurgery consult in order to exclude acute appendicitis and VP shunt tip infection. Twenty four hours later, the patient’s symptomatology improved, and she was discharged with the diagnosis of atypical colicky abdominal pain seeking a gastroenterologist consult. Discussion. This case supports that when a patient with prior VP shunting presents with right lower quadrant abdominal pain, differential diagnosis can be tricky for the surgeon. Conclusion. Apart from acute appendicitis, primary or secondary VP catheter tip infection must be considered because the latter can be disastrous.